Pengaruh kemajuan teknologi informasi terhadap perkembangan akuntansi - Eric Fauzi; Muhammad Visar Sinatrya; Nanda Daru Ramdhani; Ruhuphy Ramadhan; Zaid Muhammad Rasid Safari (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Technology that develops rapidly causes significant changes in the accounting field. These changes require accountants to continue to follow developments and improve their competence. Historically, the development of accounting has been divided into three eras, starting from the farming era and then the industrial era to the present, namely the information age. The more advanced information technology (IT), the more influence it will have on the accounting field. One of the effects of IT progress can be seen in the development of accounting information systems (AIS) in terms of processing data, internal control, and increasing the amount and quality of information in financial reporting. The development of computer-based AIS in producing financial reports also has an impact on the audit process. Although at first it gave the accounting profession a sense of worry, the development of IT in the end provided new opportunities for the accounting profession. The new opportunities that can be achieved include computer-based information system audits, computer-based information system consultants and web trust audits. Advances in IT brought significant changes to the development of accounting and also brought many benefits for both employees and companies.